ANALYSIS OF RAW MATERIALS FOR CEMENT PRODUCTION IN PT. SEMEN TONASA PANKEP - Rizal, Samsul; Nadiah, Nur; Effendi, Effendi (Jurnal Ekonomi Balance, 2018)
In 2016 amounted to 34,599 tons while the safety stock according to the min-max stock method was 5,853 tons. In 2017 the final inventory of clay raw materials was 45,694 tons while the safety stock according to the min-max stock method was 3,438 tons. In these two years, it shows that the amount of inventory of final inventory of clay raw materials is very large when compared to inventory according to the method of min- max stock. End supplies of woven paper raw materials. the final inventory of raw material for woven paper is greater than the inventory according to the min-max stock method of 2,441,774 meters while the safety stock according to the min-max stock method is 982,732 meters The final inventory of BCO raw materials in 2016 was 180,140 liters while the safety stock according to the min-max stock method was 20,534 liters. In 2017 the final inventory of BCO raw materials at PT. Semen Tonasa is 202,367 liters while the safety stock according to the min-max stock method is 10,432 liters. In these two years, it shows that the amount of inventory of final inventory of BCO raw materials is very large when compared to inventories according to the Min-max stock method